Calcium Channel Blockers Possibly Delay the Elimination of Plasma Methotrexate in Patients Receiving High-Dose Methotrexate Therapy. (2nd January 2019) - Inose, Ryo; Takahashi, Katsuyuki; Nanno, Satoru; Hino, Masayuki; Nagayama, Katsuya
Abstract : Delayed elimination of plasma methotrexate (MTX), which leads to elevated toxicity, is often observed in patients receiving high-dose methotrexate (HD-MTX) therapy, despite of the preventive measures. In this study, we investigated the factors that delay elimination of plasma MTX in patients on HD-MTX therapy. Fifteen patients who received HD-MTX therapy (21 cycles) were classified into two groups: delayed elimination of plasma MTX (38.1%, 8/21) and normal elimination of plasma MTX (61.9%, 13/21). Patient characteristics, plasma MTX concentrations, laboratory values, and adverse reactions were compared between the two groups using Fisher's exact test. Univariate analysis showed that co-administration of calcium channel blockers was significantly associated with delayed elimination of plasma MTX ( p = 0.042). This is the first report demonstrating that co-administration of calcium channel blockers may be a predictive factor of delayed elimination of plasma MTX in patients receiving HD-MTX therapy.